If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 9 = 87 + -10x Reorder the terms: 9 + 6x = 87 + -10x Solving 9 + 6x = 87 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 9 + 6x + 10x = 87 + -10x + 10x Combine like terms: 6x + 10x = 16x 9 + 16x = 87 + -10x + 10x Combine like terms: -10x + 10x = 0 9 + 16x = 87 + 0 9 + 16x = 87 Add '-9' to each side of the equation. 9 + -9 + 16x = 87 + -9 Combine like terms: 9 + -9 = 0 0 + 16x = 87 + -9 16x = 87 + -9 Combine like terms: 87 + -9 = 78 16x = 78 Divide each side by '16'. x = 4.875 Simplifying x = 4.875
| 4.95+1.95(v)=42 | | (9/4)-4x=(1/2)x | | X^2+10x+17= | | 4x-3x-10=0 | | (n-5)*10=27 | | 9-3(2x+5)+8x= | | 5lnx-3lny=0 | | y=0.1x^2-1.2x+7.6 | | 9-3(2x+5)+8x=equation | | 5-6k=5 | | (4/3)/x | | 3.14c=7927 | | 24+1=74 | | (8/2x)=(15/60) | | 3x+1+8x-9+5x-3=180 | | 27377=6786v | | 23=-4m+2-3m | | 1+4r=-15+6r | | 3x+-1=12x-64 | | 3(1/3)3 | | 5e+7e-9-e=84-4e | | (1/3)(1/3)(1/3)3=a | | 4/5y-8+=2/5+16 | | 8/2x=15/60 | | 7(k-3)= | | 2a+3b+7c= | | 3x+54y-12=0 | | 6(3-4y)= | | n+29=48 | | -4(-2b-7)=-44 | | 1.84/2.85=5.14/t | | 3i*x=y |